Effects of melatonin on apoptosis and cell differentiation in MCF-7 derived cancer stem cells - Koçak, Nadir; Dönmez, Hüseyin; Yildirim, ć°brahim Halil (Cellular and Molecular Biology, 2018)
Melatonin is a hormone of the pineal gland that has a wide range of biological effects such as antioxidant, anti-inflammatory, and anti-tumor activity. Previous studies have shown that melatonin also affects survival, proliferation, and apoptosis of the cells. In this study, we investigated the effect of melatonin on apoptosis, self-renewal, and differentiation. For this purpose, MCF-7 and HEK293 cells were subjected to melatonin treatment. Expression of genes related to apoptosis (Bax and Bcl2) and self-renewal and differentiation (Oct4, Sox2, and Nanog) analyzed after the sorting of cancer stem cells from MCF-7 cells. Results showed that the effect of melatonin is dependent on the melatonin concentration and treatment periods. Melatonin treatment decreased the cell proliferation rate of MCF-7 in contrast to HEK293. Also, this treatment increased apoptosis in MCF-7 cells and decreased in HEK293 cells. Gene expression of Nanog was decreased and Sox2 was increased in both cell groups after the melatonin treatment. Expression of Oct4 was decreased in MCF-7 cells and increased in HEK293 cells. We determined that melatonin decreases apoptosis and differentiation of stem cells in normal HEK293 stem cells, but increases apoptosis and differentiation in the MCF-7 cancer stem cells.